South Asian and European colitics show characteristic differences in colonic mucus glycoprotein type and turnover. Issue 5 (May 1995) - Probert, C S; Warren, B F; Perry, T; Mackay, E H; Mayberry, J F; Corfield, A P
Abstract : South Asians in Britain have a high incidence of ulcerative colitis and a low incidence of colorectal cancer. The pattern of mucus production in 12 South Asian and 16 European colitics and a control group of 19 South Asians was studied. Three types of mucin were identified after organ culture of colonic biopsy specimens with a dual label of [3H]-glucosamine and sodium [35S]-sulphate: type A had a high [35S]:[3H] ratio and high incorporation ([3H] dpm/micrograms DNA > 500); type B had a low ratio and high incorporation; and type C had low incorporation but with either high (C1) or low (C2) ratios. European colitic mucins show a significant reduction in the level of sulphation detected by mucin histochemistry with high iron diamine/Alcian blue staining, together with predominantly type B or C2 mucins (low sulphation). South Asian colitics showed histochemically normal patterns of high sulphation and largely type A and C1 mucins (high sulphation). There was no correlation of mucin type with disease activity index in either ethnic group. The appearance of apparently normal mucin in patients with ulcerative colitis may be a useful marker for the identification of a subgroup at low risk of colorectal cancer.